Cold three-body collisions in hydrogen--hydrogen--alkali-metal atomic systems - Wang, Yujun; D’Incao, J. P.; Esry, B. D. (My University, 2011)
We have studied hydrogen-hydrogen-alkali three-body systems in the adiabatic hyperspherical representation. For the spin-stretched case, there exists a single XH molecular state when X is one of the bosonic alkali atoms: 7Li, 23Na, 39K, 87Rb, or 133Cs. As a result, the only recombination process is the one that leads to formation of XH molecules, H+H+X→XH+H, and such molecules will be stable against vibrational relaxation. We have calculated the collision rates for recombination and collision-induced dissociation as well as the elastic cross sections for H+XH collisions up to a temperature of 0.5 K, including the partial wave contributions from JΠ=0+ to 5−. We have also found that there is just one three-body bound state for such systems for JΠ=0+ and no bound states for higher angular momenta.